Evaluation of the 30km/h speed limit trial in the City of Yarra, Melbourne, Australia. (12th October 2020) - Lawrence, B.; Fildes, B.; Thompson, L.; Cook, J.; Newstead, S.
Abstract: Objective: Safe vehicle speeds were identified as a key element in a safe system approach to road safety. The City of Yarra in Melbourne, Australia has a 40 km/h default speed limit across their municipality, but wished to reduce the speed limit in local residential streets to 30 km/h. The Monash University Accident Research Center provided Council with a design for a demonstration trial and agreed to evaluate its safety benefits over 12 months. The trial was expected to show significant reductions in speed and increased community support. Method: A before and after design was employed with a control (untreated) area to evaluate the safety outcomes of the trial. Speed limits were reduced to 30 km/h in the trial area for 12 months but kept at kept at the current 40 km/h (25 mph) limit in the control region. Vehicle speeds were measured at around 100 selected sites in the trial and control areas, and resident surveys were undertaken in both regions before and after the trial. Results: The findings showed a small but modest reduction of 1.1% in average speed in the trial region but a surprising 2.7% in the control region. On further examination, significant reductions were observed in the percent of vehicles exceeding 40 km/h (25 mph) and 50 km/h (31 mph) in both the treated and control regions, but not at 30 km/h (19 mph). A regression analysis further showed a significant treatment effect of 11% at 40 km/h and 25% at 50 km/h when adjusting for differences between treated and controls. Among other findings, the survey results found increased support for the lower speed limit of 17% with little adverse consequences. Conclusion: The findings give support for the likely safety benefits of the 30 km/h trial with increased support from the residents. Speed reductions in the control region suggested a carry-over of the effects of the trial but also added support by local residents for reduced speed limits in the region. Potential injury savings were estimated at a 4% reduction in the risk of a pedestrian injury from the observed treatment effect in the trial region.